Content-analysis of scientific and practical research areas in social pharmacy - А. А. Kotvitska; I. О. Surikova; I. V. Kubarieva (Zaporozhye State Medical University, 2019)
In many countries, social pharmacy, as a research area, is well developed, providing international and interdisciplinary collaboration in the context of discussing and disseminating health-related knowledge. Taking into account the European integration processes of reforming the domestic pharmaceutical sector of healthcare, it is important to study the international experience of the formation of social pharmacy as the direction of scientific research. Aim: analysis of scientific and practical areas of social pharmacy research. Materials and methods. The research of scientific publications of the International Journal "Research in Social and Administrative Pharmacy" for the period of 2012-2018 has been conducted using content analysis Results. The most authoritative scientific publication that covers all aspects of social pharmacy is the scientific journal "Research in Social and Administrative Pharmacy", the editorial board of which includes scientists from The United States, Australia, The United Kingdom, Canada, Portugal, Egypt, Brazil, Northern Ireland, Finland, Kosovo, New Zealand, Estonia. It is established that, for the most part, the results of original research are published (67.7 % of all publications); in addition, the publication contains review articles, brief research, proposed models. The most widespread categories in the field of social pharmacy are community pharmacy, pharmacist, pharmaceutical service, medication adherence, communication between "pharmacists - patients - physician", health literacy, pharmacotherapy safety, self-medication etc. Published materials cover study of most socially significant diseases (hypertension, asthma, diabetes, neurological diseases) with all categories of the population (children, adults, elderly, pregnant, rural population etc.) in the vast majority of countries of the world (North and South America, European countries, some African countries, Middle and Far East, Australia and New Zealand). Conclusions. Priority areas of social pharmacy research focus on social, organizational, economic, legal, psychological, and communication aspects that affect the effectiveness of pharmaceutical care and indicators of patient's life quality.